The Impact of Information Technology Governance on Financial performance (A field study on private commercial banks operating in the Syrian coast) (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The study aimed to demonstrate the impact of information technology governance in its four dimensions (planning and organization, ownership and implementation, delivery and support, and follow-up and evaluation) in improving the financial performance of private commercial banks operating in the Syrian coast.The researcher followed the descriptive analytical approach in his study, and a set of methods, including relying on secondary and primary data, through a questionnaire that was designed by informing the researcher of the published literature, and it was distributed to (245) respondents, of which (234) were recovered, and (228) were valid questionnaires For analysis, the research community consisted of a cadre of workers in the departments of branches of Syrian commercial banks, and then the SPSS program was relied on as a tool for analyzing the available data.The study reached a set of results, including: The commercial banks administration is keen to develop and maintain procedures, the commercial banks administration is keen to obtain and maintain the information technology infrastructure, the commercial banks are keen to qualify and train employees and manage their performance, and the commercial banks administration is keen to have a sufficient cadre. For the IT department.